上顎前歯部歯肉に認めた人体ハエ症の1例 - 渡邊, 裕加; 町田, 好聡; 山本, 学; 下里, 剛史; 齋藤, 翔太; 浅田, 泰幸 (日本口腔外科学会雑誌, 2018)
Human myiasis is a parasitic infestation caused by fly larvae. There are many case reports of parasitic infestations in the digestive tract, ears, and sites of traumatic injury, but few reports of infestation inside the oral cavity. We report a case of human myiasis arising in the anterior maxillary gingiva.　A 91-year-old woman was admitted to our hospital in October 2016 because of pneumonia. She started to receive antimicrobials after being hospitalized and her pneumonia symptoms were resolving, when five larvae were observed in the maxillary gingiva during oral care on hospital day 19. The larvae were extracted and sent to Japan’s National Institute of Infectious Diseases (Ministry of Health, Labour, and Welfare) for identification. They were identified as the third instar larvae of Sarcophaga similis. Based on the growth cycle of Sarcophaga similis, our patient is believed to have contracted the infestation after hospitalization. Regular, strict oral care was provided, and no insect larvae were found thereafter. Her pneumonia and oral health status improved, and she was transferred to another hospital on hospital day 35.